Proceedings of International Symposium on Oilfield Chemistry 2003
DOI: 10.2523/80230-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Inhibitor Squeeze Design

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractOil field scale treatments can become more difficult when working with deeper non-conventional wells. Inhibitor squeeze is generally the most efficient scale treatment technology. However, inhibitor squeeze treatment is based more on experiences than mechanistic understanding of how the chemical interacts with formation rock and how it flows back.Better mechanistic understanding of the phosphonate/rock interaction is needed to derive innovative squeeze treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Phosphonate chemicals show excellent scale inhibition performance, particularly in squeeze treatments. 14,15 They afforded remarkable retention and adsorption properties onto the formation rock and are easily monitored and detected. 16 In addition, polymer-based sulfonates have attracted significant attention as superior SIs in extremely high salinity reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphonate chemicals show excellent scale inhibition performance, particularly in squeeze treatments. 14,15 They afforded remarkable retention and adsorption properties onto the formation rock and are easily monitored and detected. 16 In addition, polymer-based sulfonates have attracted significant attention as superior SIs in extremely high salinity reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphonate and sulfonate-based SIs are commonly applied for downhole and topside oilfield scale management. Phosphonate chemicals show excellent scale inhibition performance, particularly in squeeze treatments. , They afforded remarkable retention and adsorption properties onto the formation rock and are easily monitored and detected . In addition, polymer-based sulfonates have attracted significant attention as superior SIs in extremely high salinity reservoirs. , It was also found that introducing a few sulfonate moieties in the polymer structure improves its thermal stability, leading to a prolonged scale inhibition performance under harsh oilfield conditions…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a low solubility crystalline phase of calcium phosphonate with a stoichiometry of Ca3H4DTPMP was successfully made by Kan et al (Kan et al 1994) from the amorphous calcium phosphonate precipitates by a combined dialysis and filtration method. Following this observation, low solubility phase of calcium phosphonate precipitates were reported for other common phosphonate inhibitor such as, NTMP, and polyphosphinocarboxylic acid (PPCA) by the same approach (Xiao et al 2001;Kan et al 2003). Fogler and his co-worker (Browning and Fogler 1996;Pairat et al 1997) demonstrated different Ca-HEDP and Ca-ATMP precipitates by changing the pH and calcium-tophosphonate molar ratios.…”
Section: Introductionmentioning
confidence: 88%
“…Others have reported on liquid inhibitor squeeze treatments. 5,6 Since a minimum residual value (for the sake of this exercise use 10 ppm as the point at which inhibition may start to diminish) is all that is necessary for scale protection, any residual in excess of that value is wasted. Thus the goal of any long term scale inhibitor exercise is to place an inhibitor into the formation such that the residual value starts low, i.e.…”
Section: Days Since Inhibitor Placement Scale Inhibitor Residual In Ppmmentioning
confidence: 99%